Expert views on metacognitive strategies for Arabic Language learning: an application of the Fuzzy Delphi method - Mustapha, Nik Hanan; Mohmad Rouyan, Nurazan; Mustapha, Nik Farhan; Daud, Nadwah; Mat Teh, Kamarul Syukri (Science Publishing Corporation, 2018)
The purpose of this paper is to seek expert opinion on the importance of each of the metacognitive strategies. It uses the Fuzzy Delphi Method which is a scientific analysis technique to obtain expert consensus on a particular issue. In this paper, ten experts in the field of Arabic language teaching from five public universities in Malaysia participated to rank the importance of nine metacognitive strategies from the Strategy Inventory for Language Learning (Oxford, 1989). Findings indicate that they agree on the importance of the know-how knowledge, superiority of planning over monitoring and evaluation as well as the need to be aware on how fluent speakers perform. This paper concludes with a discussion on the experts’ ranking in the light of Arabic language learning.